Germination Behaviour of Pea Seeds on Municipality Sewage and Some Industrial Effluents of Biratnagar - Shrestha, Mohan Kumar; Niroula, Bhabindra (Our Nature, 2006)
Municipality sewage and effluents from Dairy Farming and Shah Udyog were chosen to assess the germination activity of Pea (Pisum sativum L. var. arkel). The effluents from Municipality Sewage and Dairy Farming inhibited seed germination while Shah Udyog effluent promoted. The effluent from Municipality Sewage and Dairy Farming delayed seed germination during early hours i.e., 24 hours of sowing. The inhibition was maximum in the Municipality Sewage effluent where as the germination percentage never exceeded 48% even after 120 hours of sowing. The dilution experiment revealed that the effluent of Municipality Sewage was still inhibitory upto 25% (v/v) concentration while the inhibitory effect of Dairy Farming was overcome at 50% (v/v) concentration. The Shah Udyog effluent was safe for seed germination at all dilution. Keywords: Effluent, Seed Germination, Inhibition and Promotion doi:10.3126/on.v1i1.302 Our Nature (2003) 1: 33-36